State Repression and Political Deportation in Canada, 1919-1936 - Molinaro, Dennis (University of Toronto, 2015)
Section 98 of the Criminal Code of Canada was in force from1919 to 1936. The dissertation traces the way in which Canada incorporated emergency law, created during the First World War under the War Measures Act, into the Criminal Code as Section 98 after the war to combat political radicalism from 1919 to 1936. In contrast to existing scholarship, this work not only explains how a liberal democracy like Canada can legally use emergency legislation outside of a state of emergency through a process of `normalization' but it also examines the effects of such laws on their human targets through case studies of criminal trials and deportation hearings. Targets included political activists, immigrants and women. It makes contributions to Canada's legal, immigration, labour and intelligence history. The study also examines the international influences on Canadian policy makers in creating such laws and the complex international identities of the transnational activists at whom these laws were often directed. The work examines how culture played a crucial role in underpinning the intelligence cycle that led to the prosecution of leading Communist Party of Canada (CPC) members. It also complicates our understanding of the CPC during Moscow's `Third Period.' It was a party that both marginalized and welcomed immigrant workers. The dissertation provides an in-depth examination of the trial of Rex v. Buck et al and the ways in which political ideology was interpreted by the court as a criminal act. It examines cases of deportation that resulted from the trial, such as the case of the `Halifax Ten,' and traces what happened to the deportees after their deportation making use of Finnish, Polish, Croatian, and German primary sources. In addition, this work demonstrates how the communist led organization, the Canadian Labour Defense League (CLDL) initiated Canada's civil rights movement by joining with moderate leftists during the `Third Period,' and before the Communist International's shift to the `United Front' policy, to repeal Section 98. It demonstrates how the normalization of emergency law continued after Section 98's repeal when its core elements were retained and folded into Canada's sedition laws where it remains today.
Keywords: Section 98; communism; deportation; national security; state of emergency; state of exception